The Use of Joint Construction Upon Writing Achievement - Arlinayanti, Kadek Dwi; Sariyani, Ni Nyoman (Universitas Pendidikan Ganesha, 2022)
Mastering the language, especially English, is not enough if people can only speak fluently. Students are also required to be able to produce language in written form because writing is considered essential. This study aims to analyze the significant effect on the writing ability of students who are taught using the Joint Construction technique and those who use conventional writing techniques. This research is experimental, using the post-test only control groups design. The population of this research is 224 students. Two classes were randomly selected as the research sample. The test results were analyzed through descriptive and inferential statistics. The results of the research are descriptive analysis results. The average value of the experimental group is 79.78, while the average value of the control group is 75.66. It means that the experimental group performs better than the control group. In statistical inferential analysis, a significant difference in the writing ability of students taught using the Joint Construction technique and conventional writing techniques was 2.43. So the Null hypothesis used is rejected. It was concluded that there was a significant difference in students' writing achievement between students taught using the Joint Construction technique and those taught using conventional writing techniques.